Synthesis of Furo- and Thienoquinolines by Using an Amine Oxidase-Inspired Catalyst - Thorve, Pradip Ramdas; Maji, Biplab (Synlett, 2023)
We report the regioselective synthesis of furo- and thienoquinolines by using an amine oxidase-inspired catalyst (1,10-phenanthroline-5,6-dione) and an abundant Lewis acid (FeCl3) as a co-catalyst. The aerobic amine dehydrogenation proceeds under mild conditions and produces the quinolines in high yields. Mechanistic studies helped to identify the possible reaction intermediates and the specific role of the catalyst in the multistep cascade.
Keywords: biomimetic catalyst; iron catalysis; aerobic oxidation; dehydrogenation; quinolines